Solid liquid extraction in biorefinery. - Zainal Abidin, Zurina; Awang Biak, Dayang Radiah; Mohd.Yusoff, Hamdan; Harun, Mohd Yusof (John Wiley, 2013)
Solid–liquid extraction (SLE) is a common separation method employed in industry. Since the production of bioenergy is not directly related to SLE, this chapter focuses on bio-based products including biofuels. The chapter presents an overview of the current status of SLE in the biorefinery industry, and discusses SLE principles, process design, and modeling considerations, as well as elaborating on the industrial application of SLE by providing some examples. Finally, the economic importance and challenges of SLE are discussed. The state-of-the-art technology for SLE in the biorefinery industry involves not only the equipment design and operation, but also the process model. The development of statistical models based on experimental design and the application of various process flows is one of the new modeling approaches in SLE.